2003
DOI: 10.1210/jc.2003-030704
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Betaglycan, an Inhibin Coreceptor, in Normal Human Ovaries and Ovarian Sex Cord-Stromal Tumors and Its Regulation in Cultured Human Granulosa-Luteal Cells

Abstract: Activins and inhibins are often antagonistic in the regulation of ovarian function. TGFbeta type III receptor, betaglycan, has been identified as a coreceptor to enhance the binding of inhibins to activin type II receptor and thus to prevent the binding of activins to their receptor. In this study we characterized the expression and regulation pattern of betaglycan gene in normal ovaries and sex cord-stromal tumors and in cultured human granulosa-luteal cells from women undergoing in vitro fertilization. Expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…This TGF-␤-inducible protein (58), which can also be up-regulated upon protein kinase C activation (59), has been previously demonstrated to down-regulate the activity of activin A (60), a TGF-␤ superfamily member. Activin A has been shown to have an important role in hematopoiesis, and can inhibit colony formation by peripheral blood granulocyte-monocyte colony-forming units when stimulated with IL-3.…”
Section: Discussionmentioning
confidence: 99%
“…This TGF-␤-inducible protein (58), which can also be up-regulated upon protein kinase C activation (59), has been previously demonstrated to down-regulate the activity of activin A (60), a TGF-␤ superfamily member. Activin A has been shown to have an important role in hematopoiesis, and can inhibit colony formation by peripheral blood granulocyte-monocyte colony-forming units when stimulated with IL-3.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Woszczyk and colleagues found all three of the TGF-h receptors to have higher expression in high-grade lymphomas compared with low-grade lymphomas (7), suggesting a tumor promoting role for these receptors. A tumorigenic role for ThRIII was also suggested by studies in B-chronic lymphocytic leukemia and certain ovarian sex cord-stromal tumors (8,9). Due to this apparent contradiction and to the potential limitations of overexpression studies, we decided to investigate the role of ThRIII in breast cancer using a loss-of-function approach.…”
Section: Cancer Researchmentioning
confidence: 99%
“…Our laboratory has recently published data supporting a tumor suppressor role for ThRIII in nontumorigenic NMuMG mammary epithelial cells that is dependent on the ability of ThRIII to modulate nuclear factor-nB (NF-nB) signaling (6). In contrast, an oncogenic role for ThRIII was suggested by studies in lymphoma, B-chronic lymphocytic leukemia, and certain ovarian tumors (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…These authors have more recently shown that blocking the constitutive action of NFkB in the GCT cell lines increased the sensitivity of the cells to TGFB2 induced apoptosis while betaglycan expression reduced NFkB activity (Bilandzic et al, 2013). Liu et al (2003) reported only weak or no immunostaining of betaglycan in granulosa cell tumours, while the stromal tissue and all thecomas and fibromas had moderate to strong immunoreactivity. Therefore, betaglycan appears to be necessary for the regulation of normal granulosa cell function and a decrease in its secretion may contribute to the progression of GCT.…”
Section: Betaglycan In Ovarian Cancermentioning
confidence: 99%
“…Betaglycan increases the binding affinity of inhibin to the ACVR2 receptor and may increase the ability of inhibin to block activin signalling (Chapman and Woodruff, 2003;Lewis et al, 2000). Betaglycan mRNA is expressed in the granulosa, thecal and stromal cells of normal human ovaries and the protein in the thecal and granulosa cells of late stage follicles but not in the epithelium (Liu et al, 2003). Zhu et al (2010) reported that PCOS patients with increased inhibin B and decreased activin A concentrations in serum, also had increased betaglycan mRNA expression when compared to normal controls.…”
Section: Inhibin and Betaglycanmentioning
confidence: 99%